Southern Beaufort Sea Polar Bear Diet and Gut Microbiota Data, 2015-2019 ... - Todd C Atwood; Damian M Menning; USGS Alaska Science Center, Polar Bear Research Program (U.S. Geological Survey, 2023)
This dataset is one table with data collected and derived from polar bears sampled in Alaska's southern Beaufort Sea during 2015-2019. Data include demographic and morphometric information from each sampled polar bear, gut microbiome diversity indices derived from fecal DNA metabarcoding, and the proportion of prey species detected in individual bear diets derived from quantitative fatty acid analysis (QFASA). The presence of prey items in the diet of polar bears was also assessed using fecal DNA metabarcoding. Note that cetacean data obtained via DNA metabarcoding was not analyzed and is not presented in this data release. Only southern Beaufort Sea population data are included in this USGS data release. All DNA sequence data have been submitted to the NCBI Short Read Archive (accession bioproject ID: PRJNA773176). ...